Recent Advances in the Treatment of Non-small Cell Lung Cancer with Brigatinib - Jia YU; Shengxiang REN (Chinese Journal of Lung Cancer, 2025)
The discovery of anaplastic lymphoma kinase (ALK) tyrosine kinase gene rearrangement mutations in non-small cell lung cancer (NSCLC) has driven continuous advancements in ALK-targeted therapies. The next generation of ALK tyrosine kinase inhibitor, Brigatinib, has demonstrated significant efficacy in patients with ALK-positive NSCLC, offering clinical benefits in deep response of tumor, treatment of brain metastases patients, quality of life, and long-term survival. This review will provide current advancements and exploratory directions for Brigatinib.